2015
DOI: 10.1186/s13098-015-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and benign prostatic hyperplasia: association or coincidence?

Abstract: Background It has been suggested that individuals with metabolic syndrome (MetS) may be prone to developing benign prostatic hyperplasia (BPH), but the direction of causality remains uncertain. The objective of this cross-sectional study was to evaluate the association between BPH and MetS in men who were referred to surgery for BPH. We were interested in identifying the anthropometric, metabolic, and hormonal factors that potentially influence the risk of both conditions.MethodsThe study was conducted on 128 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 37 publications
(49 reference statements)
2
26
0
2
Order By: Relevance
“…et al, 2016). Estrogen induced stimulation of prostatic growth has also been reported in dogs and monkeys (Jeyaraj et al, 2000; Roehrborn and McConnell, 2002; Aleksandra et al, 2015). …”
Section: Etiology Of Bphmentioning
confidence: 81%
See 4 more Smart Citations
“…et al, 2016). Estrogen induced stimulation of prostatic growth has also been reported in dogs and monkeys (Jeyaraj et al, 2000; Roehrborn and McConnell, 2002; Aleksandra et al, 2015). …”
Section: Etiology Of Bphmentioning
confidence: 81%
“…Aging has been implicated as the major risk factor for the development of BPH (Roehrborn and McConnell, 2002; Aleksandra et al, 2015). Several studies have demonstrated a relationship between age and markers of BPH progression (Neuhouser et al, 2008; Liu et al, 2009).…”
Section: Etiology Of Bphmentioning
confidence: 99%
See 3 more Smart Citations